Optical Properties of Sol-Gel Deposited Barium Strontium Titanate (BaxSr1-xTiO3) Films - Lahiry, Sharmistha (Trends in Sciences, 2023)
Optical properties of sol-gel deposited Barium Strontium Titanate (BaxSr1-xTiO3, BST) thin films were studied to determine their suitability as light sensors. Crystallized BST films were formed by annealing in air at 700 °C for 1 h. Lattice parameters and grain sizes were determined for all the compositions. The band gap and refractive index values of the samples were determined from the optical transmission spectra for different compositions. Band gap of all the compositions were in the semiconductor range that would allow them to be used for photodiode and light sensor applications. Refractive index is reported for all the compositions. HIGHLIGHTS Different compositions of BaxSr1-xTiO3 with x = 0.0, .... 1.0 were deposited by sol-gel method Band gap variation with compositions is reported for both amorphous and crystalline films Refractive index variation with composition is reported for both amorphous and crystalline films Suitability of different compositions for light sensor applications are suggested from band gap and refractive index values GRAPHICAL ABSTRACT